POTENTIAL EFFECT OF FORTIFIED PAN BREAD WITH ALOE VERA JUICE ON ALLOXAN-INDUCED DIABETIC RATS - Al-Muammar, May; Elsadek, M.F.; El-Shafie, Mona (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: This study was designed to investigate (1) the potential use of Aloe vera juice (AVJ) for fortification of pan bread with evaluatesthe sensory characteristics and the nutritive value. (2) The possible beneficial role of 5% and 10% AVJ-fortified bread against diabetic rats.Materials and Methods: Bread fortified with 5%, 10% and 20% AVJ investigated with panel test and the highest two scores (5%, 10%) wererecorded and included for biological study. Forty male Albino rats weighted 200 + 10 g were divided into 4 groups (n=10) (-) control, (+)diabetic control, 5% and 10% AVJ-fortified bread.Results: Diabetic rats resulted in significant (p<0.05) increase in liver and kidney mass, blood glucose, serum hepatic biomarkers,malondialdehyde (MDA) and serum lipid profiles except serum high-density lipoprotein cholesterol (HDL-C)while serum insulin, albumin, andtotal antioxidant capacity (TAC) that had significant (p<0.05) reduction compared to control group. AVJ-fortified bread causes sufficientamelioration against the effects of diabetes with improving all tested biochemical parameters which were more pronounced in 10% AVJfortifiedgroup.Conclusions: Based on the results, it appeared that consumption of AVJ-fortified bread has reduced blood glucose, lipid profiles and hepaticbiomarkers with eliminated oxidative stress by virtue of its antioxidant properties.